2016
DOI: 10.3390/s16122154
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lateral Flow Assay Based on Size-Controlled Gold Nanoparticles for Detection of Hepatitis B Surface Antigen

Abstract: In this study, we developed lateral flow assay (LFA) biosensors for the detection of hepatitis B surface antigens using well-controlled gold nanoparticles (AuNPs). To enhance colorimetric signals, a seeded growth method was used for the preparation of size-controlled AuNPs with a narrow size distribution. Different sizes of AuNPs in the range of 342–137.8 nm were conjugated with antibodies and then optimized for the efficient detection of LFA biosensors. The conjugation stability was investigated by UV-vis spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…However, EM is certainly inappropriate for routine clinical diagnosis because of the required time and cost, as well as many safety concerns. Furthermore, although the simple structure of virus particles allows the features of diagnostic relevance to be easily defined and tested, it presents limitations on the use of their characteristics for practical applications, especially with the increasing number of discovered viruses and recorded viral infections 14 , 16 , 17 . In addition, this structural simplicity confers viruses with rapid rates of spontaneous adaptation and evolution that may occur through direct genetic mutation, genetic substitution, or recombination.…”
Section: Viruses: Nanoscale Pathogens With a Global Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, EM is certainly inappropriate for routine clinical diagnosis because of the required time and cost, as well as many safety concerns. Furthermore, although the simple structure of virus particles allows the features of diagnostic relevance to be easily defined and tested, it presents limitations on the use of their characteristics for practical applications, especially with the increasing number of discovered viruses and recorded viral infections 14 , 16 , 17 . In addition, this structural simplicity confers viruses with rapid rates of spontaneous adaptation and evolution that may occur through direct genetic mutation, genetic substitution, or recombination.…”
Section: Viruses: Nanoscale Pathogens With a Global Burdenmentioning
confidence: 99%
“…A strip composed of a sample pad, conjugation pad, control line, test line and absorbent pad was used to capture HBsAg labeled with AuNPs and the test line becomes red in color. The results showed that the signal visibility of LFA could be improved by increasing the diameter of AuNPs, and ~43 nm AuNP enabled LFA assay with a detection limit of 100 ng/mL 16 .…”
Section: Detection Of Specific Viruses Using Aunpsmentioning
confidence: 99%
“…Research is also being conducted on other types of nanoparticle-based sensing devices for bacterial pathogens, virus particles, hazardous chemicals, toxic proteins, peptides, and other entities ( Kim et al, 2016a , b ). Figure 3 represents the evolution of various kinds of liposome nanoparticles for their potential commercial usage.…”
Section: Liposome Nanoparticles As Detection Sensor In Food Sectormentioning
confidence: 99%
“…Several studies suggest that the main disadvantage of such tests, that of their low sensitivity, can be improved by AuNP-based signal amplification [ 43 ]. Kim et al developed an AuNP-based LFA that could detect 500 ng/mL HBsAg in whole blood, which was comparable to a commercially available HBsAg LFA (Humasis, Anyang, Republic of Korea) [ 44 ].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%